CHARACTERISTICS OF THE MIXTURE OF LATASTON (HRS-WC) WITH DOLOMITE LIMESTONE AS A FILLER IN ASPHALT MIXTURE - Sulistiyono, Adi; Said, Said; Azwansyah, Heri (Fakultas Teknik Universitas Tanjungpura, 2023)
Indonesia is a country that has a lot of natural resources; one of the natural resources in Indonesia is lime. In Palembang, there is a large-scale dolomite lime-producing company that covers the territory of Indonesia. The content in the dolomite lime is Magnesium Oxide (MgO) â‰¥ 18% and Calcium Oxide (CaO) ± 30%. The purpose of this study is to utilize dolomite lime as a mixture of asphalt concrete layers and to find out changes in the characteristics of the HRS-WC mixture due to the use of dolomite lime as a filler. The experiment refers to Bina Marga 2018 revision II. The method used in this study is the experimental method, which is carried out by conducting experimental activities to obtain data. The aggregate specific gravity test obtained more than 2.5 gr/cm3 results, which qualify the 2018 Bina Marga revision II specifications. Examination of the wear of the coarse aggregate yielded results that fulfil the 2018 Bina Marga revision II specifications. The filler used in this mixture is applied on combination with a percentage of 0% rock ash and 100% dolomite lime, then 25% rock ash and 75% dolomite lime, then 50% rock ash and 50% dolomite lime, then 75% rock ash and 25% dolomite lime, and 100% rock ash and 0% dolomite lime. %. The Marshall results from the percentage of 100% rock ash filler content and the percentage of 0% OAC dolomite lime filler content of 6.5% obtaine a stability value of 914.821 Kg, a flow value of 3.45 mm, and a Marshall Quotient value of 265.286 Kg/mm. The volumetric value of the percentage of 100% rock ash filler content and the percentage of dolomite lime filler content of 0 % OAC 6.5% deliver a VIM value of 4.153%, a VMA value of 18.391%, a VFB value of 79.671%.